Whole-Cell Screening-Based Identification of Inhibitors against the Intraphagosomal Survival of Mycobacterium tuberculosis - Khare, Garima (American Society for Microbiology, 2013)
We describe here an efficient strategy that employs whole-cell-based screening and further short listing of the compounds by cytotoxicity- and fluorescence-based intracellular assays, resulting in potential bactericidal hits against the growth of Mycobacterium tuberculosis in broth culture as well as in phagosomes. These compounds also inhibited multidrug-resistant strains of M. tuberculosis but showed no or poor inhibition of nonpathogenic mycobacteria or other bacterial species such as Escherichia coli.